Controllable Blinking‐to‐Nonblinking Behavior of Aqueous CdTeS Alloyed Quantum Dots. Issue 7 (15th January 2014) - Dong, Chaoqing; Liu, Heng; Zhang, Aidi; Ren, Jicun
Abstract Semiconductor quantum dots (QDs) are very important optical nanomaterials with a wide range of potential applications. However, the blinking of single QDs is an intrinsic drawback for some biological and photoelectric applications based on single‐dot emission. In this work, we systematically investigated the effects of certain synthetic conditions on the blinking behavior of aqueous CdTeS alloyed QDs, and observed that blinking behaviors of QDs were able to be controlled by the structure and concentration of the thiol compounds that were used as surface ligands. In optimal conditions, completely nonblinking QDs were prepared using certain thiol ligands as stabilizers in aqueous phase. The suppressed blinking mechanism was mainly attributed to elimination of QDs surface traps by coordination of thiol ligands with vacant Cd atoms, formation of appropriate CdS coating on QDs, and controlling the growth dynamics of QDs. Nonblinking QDs show high quantum yield, small size, and good solubility, and will be applied to some fields that were previously limited by blinking of traditional QDs.